POPULATION DYNAMICS ON ONGOLE GRADE CATTLE IN KEBUMEN REGENCY - CENTRAL JAVA - J. Rohyan; S. Sutopo; E. kurnianto (Diponegoro University, 2016)
The objectiveof this study was to elucidatereproductive characteristics, potential output and dynamics population of Ongole Gradecattle in Kebumen Regency, Province of Central Java. The studywasconductedfromSeptemberto November 2015.The materials used in the study were165 farmers as respondentshavingOngole Gradecattle. The research method used was survey. Respondent samples were taken from five districts in which the location was determined by using purposive sampling. Data were collected through direct interviews with livestock farmers as respondents. The analysis used wasdescriptive analysis. The results showed that the age at first mating was 26.87 month, S/C was 1.64, post-partum mating was4.52 month, weaning age was 3.97 month, calving interval was 14.32 month, and the birth rate topopulation was45.5%. Reproductive efficiency value was 91.8%, natural increase was 44.68%, and net replacement rate of bull and heifer were 1,209% and 253%,respectively, andtotal output 44.11%. Population dynamics of Ongole Gradecattle from 2009 to 2014 fluctuated with average growthwas -4.84%. In 2019, cow population of Ongole Gradewasestimated about 68.381 heads. In conclusion Kebumen Regencyhasa relatively high potential output of Ongole Gradecattle thatis44.11% and population dynamics from 2010 to 2014 fluctuated with average of decrease growth is 4.84%. Estimation of cow’s population of Ongole Grade cattle willincrease 16.7% per year.